Intercropping With Peppermint Increases Ground Dwelling Insect and Pollinator Abundance and Decreases Drosophila suzukii in Fruit - Gowton, Chelsea Megan; Cabra-Arias, César; Carrillo, Juli (Frontiers in Sustainable Food Systems, 2021)
Intercropping can be used to reduce pest insects within agricultural systems, e.g., through deterring pests directly or by increasing habitat for their natural enemies. For example, plant produced volatile organic compounds (VOCs) can deter or confuse host-finding by insects through olfactory disruption. Drosophila suzukii is an invasive fruit fly of agricultural concern as it can lay its eggs in both ripening and fresh fruits and, uses olfactory cues to identify its wide range of host plants. Peppermint plants (Mentha × piperita) produce high levels of VOCs while growing and may, therefore, be suitable as an intercrop to reduce D. suzukii infestations in the field, as peppermint essential oil VOCs have previously been shown to deter D. suzukii in olfactory trials. We conducted a field intercropping experiment to evaluate the effectiveness of peppermint plants compared to traditional ryegrass/clover mixes in reducing D. suzukii oviposition in the field, and the effect of peppermint intercrops on other invertebrates. In the field, we monitored sentinel fruit baits weekly for D. suzukii infestation. Additionally, we monitored intercropping effects on the invertebrate community through weekly pitfall trap collection and through a pollinator point survey. We monitored for local, farm level presence of D. suzukii through apple cider vinegar traps within crop fields and along hedgerows and found high abundance of D. suzukii (>3,000 individuals trapped). Peppermint intercrops had fewer D. suzukii emerge from fruit baits and supported greater beneficial insect abundance (predators and pollinators) compared to ryegrass/clover. However, levels of D. suzukii were low across both intercrop types. Overall, we found that peppermint intercrops could be a potential aromatic intercrop used to reduce D. suzukii adult emergence from fruit compared to conventional ryegrass/clover mixes, however this trial should be replicated over multiple growing seasons, geographic locations, and host fruits. Furthermore, further study should determine the effects of the intercrop on the focal crop of interest.